2021
DOI: 10.1111/irel.12292
|View full text |Cite
|
Sign up to set email alerts
|

Are workers rewarded for inconsistent performance?

Abstract: This paper examines whether workers are rewarded for inconsistent performance by salary premia. Some earlier research suggests that performance inconsistency leads to salary premia, while other research finds premia for consistent performance. Using detailed salary and performance data for top‐level footballers in Italy’s Serie A, we find that inconsistency is penalized for some important dimensions of basic performance measures associated with key skills of players, specifically clearances, aerial duels won, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…If a worker's productivity over time has a large component of idiosyncratic variance, then it is plausible that firms will pay more to workers with more available past performance data. There is evidence from sports labor markets that firms pay more to consistent performers (e.g., Deutscher et al., 2017; Özdemir et al., 2022), at the same time as over‐valuing recent performance (e.g., Healy, 2008). In other labor markets, Kuhnen and Oyer (2016) found that firms are more likely to hire MBA graduates who have previously worked in the same industry, suggesting some level of risk aversion.…”
Section: The Age‐wage‐productivity Puzzlementioning
confidence: 99%
“…If a worker's productivity over time has a large component of idiosyncratic variance, then it is plausible that firms will pay more to workers with more available past performance data. There is evidence from sports labor markets that firms pay more to consistent performers (e.g., Deutscher et al., 2017; Özdemir et al., 2022), at the same time as over‐valuing recent performance (e.g., Healy, 2008). In other labor markets, Kuhnen and Oyer (2016) found that firms are more likely to hire MBA graduates who have previously worked in the same industry, suggesting some level of risk aversion.…”
Section: The Age‐wage‐productivity Puzzlementioning
confidence: 99%